Pola Berpikir Serialist Siswa Dengan Kemampuan Matematis Tinggi Dalam Menyelesaikan Masalah Aritmatika Sosial Kelas VII SMPN 1 Ngantru - Marchel Akbar Putra; Sutopo Sutopo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research is caused by the mindset of students with high mathematical abilities in solving mathematical problems, especially social arithmetic, where the serialist pattern is characterized by working with procedural and operational abilities and taking a local approach. The findings in partner schools are that the majority of students work on questions according to what is taught, starting from writing down the elements in the questions, sorting out which formula is right to writing valid conclusions on the answer sheet. This study aims to describe the Serialist thinking patterns of students with high mathematical abilities in solving Social Arithmetic problems for class VII students of SMPN 1 Ngantru. This research is a descriptive qualitative research with a case study approach. The subjects in this research activity were class VII of three students at SMPN 1 Ngantru. Data collection techniques were carried out by providing test questions and open interviews. Data analysis through three steps, namely data reduction, data presentation, and drawing conclusions. The results of the research show that in the process of solving problems students with serialist thinking skills tend to understand problems in an orderly and systematic manner which can be seen on the answer sheets of each subject. Students tend to work on questions according to the information that has been presented and then process and produce the right answers.